Gene expression profiling combined with functional analysis identify integrin beta1 (ITGB1) as a potential prognosis biomarker in triple negative breast cancer. (February 2016) - Klahan, Sukhontip; Huang, Wan-Chen; Chang, Che-Mai; Wong, Henry Sung-Ching; Huang, Chi-Cheng; Wu, Mei-Shin; Lin, Yu-Chiao; Lu, Hsing-Fang; Hou, Ming-Feng; Chang, Wei-Chiao
Graphical abstract: Abstract: Triple negative breast cancer (TNBC) accounts for approximately 15–20% of all types of breast cancer, and treatment is still limited. This type of breast cancer shows a high risk of recurrence, visceral metastasis, a worse prognosis, and shorter distant metastasis-free survival. Several studies have been reported that genetics factors are associated with breast cancer disease progression and patients' survival. In this study, we combined Taiwanese microarray data from the GEO database and The Cancer Genome Atlas (TCGA) database to study the role of Integrin Beta1 (ITGB1) in TNBC. Two triple negative breast cancer cell lines (MDA-MB-231; MDA-MB-468) were used to validate the functions of ITGB1. We found that a higher ITGB1 gene expression level was associated to lower survival. Silencing of ITGB1 inhibited TNBC cell migration, invasion and store-operated calcium influx. Our study provided a potential candidate biomarker for breast cancer cells migration, invasion and TNBC patients' survival.